Epistemologi Muatan Lokal: Objektifikasi Kebudayaan Sebagai Konten Kurikulum Nasional Indonesia - Dwi Saputra, Kurniawan (University of Muhammadiyah Malang, 2024)
Within the context of modern education that prioritizes the acquisition of scientific knowledge, the existence of Muatan Lokal (local content) requires a valid epistemological foundation and mechanism. The objective of this research is to propose an epistemological framework for incorporating Muatan Lokal into the national curriculum of Indonesia. The qualitative approach employed in this study follows a hermeneutic philosophical process. The research method is literature study with literature sources and literature review as method of collecting data. The study contends that constructivism serves as underlying philosophy for the advancement of culturally oriented education, as it perceives knowledge as context-dependent phenomenon influenced by language. Consequently, within the curriculum, local content learning is proposed as the medium to bridge scientific knowledge into the cultural context of Indonesia communities. In practical terms, Kuntowijoyo’s theoretical framework facilitates the integration of indigenous content into the curriculum through the objectification process encompassing the interpretation, critical-dialectic analysis, and community acceptance.